The thrombopoietin mimetic JNJ-26366821 increases megakaryopoiesis without affecting malignant myeloid proliferation. Issue 10 (23rd August 2020) - Adrianzen-Herrera, Diego; Choudhary, Gaurav; Gordon-Mitchell, Shanisha; Ramachandra, Nandini; Bhagat, Tushar; Zhang, Hui; Aluri, Srinivas; Shastri, Aditi; Steidl, Ulrich; Will, Britta; Yang, Weng-Lang; Mahler, Michelle; et al.
Abstract: Thrombocytopenia remains a challenge in myeloid malignancies, needing safer and more effective therapies. JNJ-26366821, a pegylated synthetic peptide thrombopoietin (TPO) mimetic not homologous to endogenous TPO, has an in-vitro EC50 of 0.2 ng/mL for the TPO receptor and dose dependently elevates platelets in volunteers. We demonstrate that JNJ-26366821 increases megakaryocytic differentiation and megakaryocytic colony formation in healthy controls and samples from myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). JNJ-26366821 had no effect on proliferation of malignant myeloid cell lines at doses up to 1000 ng/mL and malignant patient-derived mononuclear cells showed no increased cell growth or leukemic colony formation capacity at concentrations between 0.2 ng/mL and 10 ng/mL. Furthermore, JNJ-26366821 did not enhance in-vivo engraftment of leukemic cells in an AML xenotransplantation murine model. Our results show that JNJ-26366821 stimulates megakaryopoiesis without causing proliferation of the malignant myeloid clones in MDS/AML and provides the rationale for clinical testing of JNJ-26366821 in myeloid malignancies.